The mitochondrial deoxyguanosine kinase is required for cancer cell stemness in lung adenocarcinoma. Issue 12 (21st October 2019) - Lin, Shengchen; Huang, Chongbiao; Sun, Jianwei; Bollt, Oana; Wang, Xiuchao; Martine, Eric; Kang, Jiaxin; Taylor, Matthew D; Fang, Bin; Singh, Pankaj K; Koomen, John; Hao, Jihui; et al.
Abstract: The mitochondrial deoxynucleotide triphosphate (dNTP) is maintained by the mitochondrial deoxynucleoside salvage pathway and dedicated for the mtDNA homeostasis, and the mitochondrial deoxyguanosine kinase (DGUOK) is a rate‐limiting enzyme in this pathway. Here, we investigated the role of the DGUOK in the self‐renewal of lung cancer stem‐like cells (CSC). Our data support that DGUOK overexpression strongly correlates with cancer progression and patient survival. The depletion of DGUOK robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self‐renewal. Mechanistically, DGUOK is required for the biogenesis of respiratory complex I and mitochondrial OXPHOS, which in turn regulates CSC self‐renewal through AMPK‐YAP1 signaling. The restoration of mitochondrial OXPHOS in DGUOK KO lung cancer cells using NDI1 was able to prevent AMPK‐mediated phosphorylation of YAP and to rescue CSC stemness. Genetic targeting of DGUOK using doxycycline‐inducible CRISPR/Cas9 was able to markedly induce tumor regression. Our findings reveal a novel role for mitochondrial dNTP metabolism in lung cancer tumor growth and progression, and implicate that the mitochondrial deoxynucleotide salvage pathway could be potentially targeted to prevent CSC‐mediated therapy resistance and metastatic recurrence. Synopsis: Elimination of slow‐cycling cancer stem‐like cell (CSC) is a major challenge for conventional cancer therapy. This study proposes that DGUOK, a rate‐limiting enzyme in the mitochondrial deoxynucleoside salvage pathway, is required for the self‐renewal of CSC in lung adenocarcinoma. DGUOK overexpression in lung adenocarcinoma was correlated with metastatic progression and worse survival. DGUOK was critical for mitochondrial DNA homeostasis and mitochondrial OXPHOS in lung cancer cells. DGUOK abrogation inhibited CSC self‐renewal by activation of AMPK and inhibition of YAP1. DGUOK targeting effectively inhibited lung cancer metastasis and induced tumor regression in xenograft lung cancer models. Abstract : Elimination of slow‐cycling cancer stem‐like cell (CSC) is a major challenge for conventional cancer therapy. This study proposes that DGUOK, a rate‐limiting enzyme in the mitochondrial deoxynucleoside salvage pathway, is required for the self‐renewal of CSC in lung adenocarcinoma.